The mediating effect of tacit knowledge sharing on the relationship between perceived supervisor support and innovative behaviour among nurses in a Malaysian public teaching hospital - Justin Wah, Nur Constance Rinen; Zawawi, Dahlia; Raja Yusof, Raja Nerina; Sambasivan, Murali; Karim, Jalina (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Drawing upon social exchange theory, this study tested tacit knowledge sharing as a mediator of the relationship between perceived supervisor support and innovative behaviour. A sample of 339 nurse-supervisor dyads from a Malaysian public teaching hospital was selected for the distribution of questionnaire. Using the structural equation modeling (SEM), the following significant relationships are concluded: (1) perceived supervisor support on tacit knowledge sharing, (2) perceived supervisor support on innovative behaviour, (3) tacit knowledge sharing on innovative behaviour, and (4) the mediating role of tacit knowledge sharing. The current study adds significantly to the body of knowledge on social exchange theory and can help teaching hospital hospital supervisors to support nurses by providing proper direction to develop effective workplace relationship between nurses and supervisors in achieving innovative behaviour.